2022
DOI: 10.20473/jfiki.v9i32022.252-261
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Feeling Lonely and Received Social Support on Medication Adherence in Elderly with Hypertension

Abstract: Background: Hypertension is currently a non-contagious disease that primarily affects the elderly population in Indonesia. Medication adherence is critical in managing hypertension and reducing the risk of morbidity and mortality. Previous research has found that loneliness and support received by older adults with hypertension influence medication adherence. Objective: This study aimed to examine the impact of feeling lonely and receiving social support on medication adherence in the elderly with hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Therefore, it is crucial for patients have high levels of medication adherence. However, that is not always the case, since there are multiple factors that affect medication adherence including social and economic circumstances, self-confidence, doctor-patient relationships, psychological aspects, complications related to hypertension, and various individual and social determinants [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial for patients have high levels of medication adherence. However, that is not always the case, since there are multiple factors that affect medication adherence including social and economic circumstances, self-confidence, doctor-patient relationships, psychological aspects, complications related to hypertension, and various individual and social determinants [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous quantitative studies have shown that social support was essential to medication adherence in the senior population [ 17 20 ]. However, there was scarcely discussion on how seniors perceived and received social support and how understanding that support could equip pharmacists for their practice.…”
Section: Introductionmentioning
confidence: 99%